Exploring the Feminity and Socio-Cultural Identity Crisis: Exploring Femininity and Socio-Cultural Identity Crisis in Indian English Literature (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper seeks to reveal the notions and aspects that are pertinent in exploring the Feminity in the context of social culture. It studies the existence of women in terms of gender, class and oppression that meted out to them in society and culture. The objective is also to trace the feminist ideology in exploring the sensibility of feminists and society towards women in Indian English literature. It explores women with a deep sensibility in the core of society and culture especially after independence. This paper presents social phases, impact of waves of feminism in Indian circumstance, quest for an identity and also the struggle for the individuality. It attempts to trace the sphere of Indian English literature which presents women in a liberal way. On the other edge especially in Western culture, they have been explored through radical mannerism. Indian culture is deeply rooted and associated with women in terms of fulfilling the rituals and customs. Today, the advocacy has assumed a vital role in the context of the world in representing women. It has become a global movement and known as “global feminism.” Now, this questions even for the existence of men in to the lives of women. Feminist ideology has converted into radical approach.